A COMPREHENSIVE ANALYSIS OF LEARNING STYLES AND THEIR IMPACT ON EDUCATION - Davronova Marjona Sherzod qizi (TADQIQOTLAR, 2025)
Abstract. This article explores the concept of learning styles and their impact on  education.  It  examines  various  models,  including  VARK,  Gardner’s  Multiple Intelligences, and Kolb’s Experiential Learning Theory. Through a detailed analysis of research  methodologies,  the  study  highlights  how  different  learning  preferences influence  academic  performance.  This    also  discusses  statistical  and  algorithmic approaches  used  to  identify  learning  styles.  The  findings  suggest  that  while individualized learning approaches can enhance student engagement and success, a flexible teaching strategy is most effective.